Policy dispatching to avoid blockages in flexible manufacturing cells type multi-reentrant - Murillo-Soto, Luis Diego (2013)
A Flexible Manufacturing Cell (FMC) can be modeled using relevant theory of discrete event systems.  The FMC integrates a set of resources, operations and materials that was combined to product processing.  If those resources are not adequately controlled, the FMC will be blocked. In order to avoid such blocking, this paper presents four guidelines to build a resource allocation policy from basic study of circular wait and production priorities. To develop a theoretical CMF raised by Peng and Zhou (2003), and from the proposed guidelines was constructed a dispatch policy. The policy was tested through simulations of the FMC, and as a result, the policy allocations were performed properly for the assembly of the parts.